Molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from chromosome 8 or r(8)(::p12→q13.1::) associated with phenotypic abnormalities - Chih-Ping Chen; Shuan-Pei Lin; Yi-Hui Lin; Schu-Rern Chern; Peih-Shan Wu; Yen-Ni Chen; Shin-Wen Chen; Chien-Wen Yang; Wen-Lin Chen; Wayseen Wang (Elsevier, 2016)
Objective: We present molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome (sSMC) derived from chromosome 8. Materials and Methods: A 35-year-old woman underwent amniocentesis at 16 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XY,+mar[20]/46,XY[39]. However, array comparative genomic hybridization analysis on the subcultured amniocytes revealed no genomic imbalance. Prenatal ultrasound showed bilateral ventriculomegaly, intrauterine growth restriction, and an enlarged right atrium. At 36 weeks of gestation, a 2380-g baby was delivered with mild facial dysmorphism. The baby postnatally manifested right hydronephrosis, vesicoureteral reflux, hypospadias, hypotonia, strabismus, developmental delay and mild mental retardation. Array comparative genomic hybridization and metaphase fluorescence in situ hybridization analyses were performed on the peripheral blood to determine the origin and mosaicism of the sSMC, and quantitative fluorescent polymerase chain reaction was used to exclude uniparental disomy. Results: The blood had a karyotype of 47,XY,+mar[17]/46,XY[23]. Array comparative genomic hybridization revealed arr 8p12q13.1 (33,476,753-67,428,722) × 2.40 (Log2 ratio = 0.24) encompassing 98 Online Mendelian Inheritance in Man (OMIM) genes including CHD7, consistent with 30-40% mosaicism for r(8)(::p12→q13.1::). Metaphase fluorescence in situ hybridization identified the sSMC(8) in 21/33 of cultured lymphocytes. Quantitative fluorescent polymerase chain reaction excluded uniparental disomy 8. Conclusion: Mosaic sSMC(8) derived from r(8)(::p12→q13.1::) can present phenotypic abnormalities. Chromosome 8q12 duplication syndrome should be included in differential diagnosis when an sSMC(8) contains 8q12.2 and CHD7.